2004
DOI: 10.1111/j.1479-828x.2004.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and birth outcome: New Zealand trends 1980–2001: Part 2. Pregnancy outcomes for Maori women

Abstract: While high rates of teenage pregnancy amongst Maori women appear not to confer additional risk for preterm birth or SGA, the social consequences of early childbearing may well be significant. The persistence of elevated rates of preterm birth and large socioeconomic gradients in SGA amongst Maori suggest that broader social and policy interventions are necessary if Maori are to achieve optimal birth outcomes in the coming decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 4 publications
1
26
0
Order By: Relevance
“…A recent series of publications [8][9][10][11] reported that women of Pacific Island and Indian ethnicity had higher rates of stillbirth compared with European women. This study used national datasets that contained limited information about maternal demographics, and no data about previous pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…A recent series of publications [8][9][10][11] reported that women of Pacific Island and Indian ethnicity had higher rates of stillbirth compared with European women. This study used national datasets that contained limited information about maternal demographics, and no data about previous pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Previously described risk factors for SGA by population centiles include short stature, low body mass index (BMI), cigarette smoking, hypertensive diseases and Asian and Māori ethnicity. [13][14][15] However, obesity has usually been found to be protective for SGA when defined by population centiles. 13,16,17 One previous study in a general obstetric population has reported obesity as a risk factor for customised SGA (adjusted for a limited number of clinical factors), 18 while risk factors for SGA infants by customised centiles have only been previously reported in a healthy, nulliparous cohort that may not be generalisable to a general population.…”
Section: Introductionmentioning
confidence: 99%
“…Maori women are recognised to be socioeconomically disadvantaged with high rates of smoking, growth restriction and preterm birth compared to New Zealand European women. 16 In contrast, Chinese ethnicity was associated with a significantly decreased risk of neonatal death. Others have also reported perinatal mortality in Chinese mothers to be lower than 32,33 or similar to that for Caucasian mothers.…”
Section: Discussionmentioning
confidence: 92%
“…14 Locally, a recent series of New Zealand papers has highlighted the effect of maternal ethnicity and socioeconomic status on perinatal outcomes, including preterm birth, growth restriction and late fetal death. [15][16][17][18] However, at present, there are few published data 4,19 on the influence of ethnicity on neonatal death in New Zealand. Furthermore, these data are either not contemporary 19 or include small numbers of deaths in Maori and Pacific Island infants.…”
Section: Introductionmentioning
confidence: 96%